Study on Flow and Heat Transfer Characteristics of Battery Thermal Management System with Supercritical CO2 for Energy Storage Stations - Ya Wang; Fengbin Li; Feng Cao; Shaozhong Liang; Jian Fu (Energies)
Energy storage stations (ESSs) need to be charged and discharged frequently, causing the battery thermal management system (BTMS) to face a great challenge as batteries generate a large amount of heat with a high discharge rate. Supercritical carbon dioxide (SCO2) is considered a promising coolant because of its favorable properties, including non-flammability, high dielectric strength and low cost for the BTMS. The heat of a battery can be absorbed to a great extent if there is a small temperature rise because as the fluid temperature approaches a pseudo-critical temperature, the specific heat capacity of SCO2 reaches its peak. In this study, a periodic model of the unit BTMS is established, and a numerical simulation is implemented to investigate the effects of different boundary conditions on the heat dissipation of a battery pack. The flow and heat transfer characteristics of SCO2 in the liquid cold plate (LCP) of a battery pack with an extreme discharge rate are revealed. The results show that SCO2 is more preferably used as a coolant compared to water in the same conditions. The maximum temperature and the temperature difference in the battery pack are reduced by 19.22% and 79.9%, and the pressure drop of the LCP is reduced by 40.9%. In addition, the heat transfer characteristic of the LCP is significantly improved upon increasing the mass flow rate. As the operational pressure decreases, the pressure drops of SCO2 decrease in the LCP. Overall, the maximum temperature and the temperature difference in the battery pack and the pressure drops of the LCP can be effectively controlled by using a coolant made out of SCO2. This study can provide a reference for the design of BTMSs in the future.